Late‐Stage Peptide Diversification through Cobalt‐Catalyzed C−H Activation: Sequential Multicatalysis for Stapled Peptides. (9th January 2019) - Lorion, Mélanie M.; Kaplaneris, Nikolaos; Son, Jongwoo; Kuniyil, Rositha; Ackermann, Lutz
Abstract: Bioorthogonal late‐stage diversification of structurally complex peptides has enormous potential for drug discovery and molecular imaging. In recent years, transition‐metal‐catalyzed C−H activation has emerged as an increasingly viable tool for peptide modification. Despite major accomplishments, these strategies largely rely on expensive palladium catalysts. We herein report an unprecedented cobalt(III)‐catalyzed peptide C−H activation, which enables the direct C−H functionalization of structurally complex peptides, and sets the stage for a multicatalytic C−H activation/alkene metathesis/hydrogenation strategy for the assembly of novel cyclic peptides. Abstract : C‐H‐Aktivierung ermöglicht Metathese : Eine bioorthogonale C‐H‐Aktivierung von Peptiden gelingt mit luft‐ und feuchtigkeitsbeständigen Cobaltkatalysatoren. Die Reaktion ebnet den Weg für eine C‐H‐Funktionalisierungs‐Olefinmetathese‐Sequenz zum Aufbau komplexer cyclischer Peptide.